2013
DOI: 10.1097/ajp.0b013e3182778153
|View full text |Cite
|
Sign up to set email alerts
|

Mental Defeat Predicts Distress and Disability in Hong Kong Chinese with Chronic Pain

Abstract: These findings provide further evidence that MD is a factor that differentiates treatment-seeking from nontreatment-seeking individuals with CP. They also highlight the potential value of applying this psychological concept to the understanding and treatment of CP in HK Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Psychological distress is associated with poor physical outcomes such as functional disability and pain [ 27 ] although the relationship is undoubtedly complex. Tang et al [ 28 ] found the presence of mental defeat was a significant predictor of functional disability and distress among individuals with CP. This may result in a cyclical experience of distress and pain, especially for CP patients who demonstrated increased distress when compared to RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress is associated with poor physical outcomes such as functional disability and pain [ 27 ] although the relationship is undoubtedly complex. Tang et al [ 28 ] found the presence of mental defeat was a significant predictor of functional disability and distress among individuals with CP. This may result in a cyclical experience of distress and pain, especially for CP patients who demonstrated increased distress when compared to RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al 10 reported a significant correlation between MD and pain interference, sleep disturbance, anxiety, depression, functional disability and psychosocial disability and in a later paper found MD was a significant predictor of both functioning and distress. 11 However, these papers did not examine whether there was a direct association between MD and pain symptomatology. Only one study has specifically examined this; García-Campayo et al 12 found a significant association between levels of MD and pain intensity in a Spanish sample of patients with fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were excluded if no intervention was discussed. Patients were required to undergo treatment because many studies have shown that patients who do not seek treatment may differ from those who do (Hartzell et al., ; Tang, Goodchild, Hester, & Salkovskis, ; Tang, Shum, Leung, Chen, & Salkovskis, ; Watkins, Wollan, Melton, & Yawn, ). This bias was eliminated from the review by requiring intervention for CLBP.…”
Section: Methodsmentioning
confidence: 99%